2021
DOI: 10.1007/s12652-021-02967-7
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 classification using deep feature concatenation technique

Abstract: Detecting COVID-19 from medical images is a challenging task that has excited scientists around the world. COVID-19 started in China in 2019, and it is still spreading even now. Chest X-ray and Computed Tomography (CT) scan are the most important imaging techniques for diagnosing COVID-19. All researchers are looking for effective solutions and fast treatment methods for this epidemic. To reduce the need for medical experts, fast and accurate automated detection techniques are introduced. Deep learning convolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…Deep learning has played an important role in medical imaging during the last decade [ 29 , 30 ]. The CV researchers have introduced many techniques for classifying medical infections like COVID-19, cancers of different types (skin, stomach, and lung), and brain tumors [ 31 , 32 ]. Recently, Abbas et al [ 33 ] implemented a deep Convolutional Neural Network (CNN) framework named DeTraC to diagnose the COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning has played an important role in medical imaging during the last decade [ 29 , 30 ]. The CV researchers have introduced many techniques for classifying medical infections like COVID-19, cancers of different types (skin, stomach, and lung), and brain tumors [ 31 , 32 ]. Recently, Abbas et al [ 33 ] implemented a deep Convolutional Neural Network (CNN) framework named DeTraC to diagnose the COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the experiments for COVID-19/non-COVID-19 and COVID-19 pneumonia/other pneumonia classifications are shared in Tables 6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,and 31. In this section, the results are evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have tried to find COVID-19 infections in CXR images by using different DL methods [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], as indicated in Table 1 . The investigation of COVID-19 identification and diagnostic systems that rely on CXR images indicated that there are still a number of vulnerabilities that need additional investigation.…”
Section: Related Workmentioning
confidence: 99%